Synthesis and Properties of UV-Curable Polyfunctional Polyurethane Acrylate Resins from Cardanol - Hu, Yun (ACS Omega, 2019)
[Image: see text] A novel UV-curable polyurethane acrylate (PUA) oligomer was synthesized by modifying cardanol with a polyfunctional acrylate precursor obtained through reacting pentaerythritol triacrylate with isophoronediisocyanate. Chemical structures of the obtained cardanol-based PUA (C-PUA) oligomer were confirmed by Fourier transform infrared and (1)H NMR. Subsequently, viscosity and gel content of the C-PUA resins containing different quantities of hydroxymethyl methacrylate (HEMA) were characterized. The C-PUA oligomer possessed a viscosity of 8360 mPa s, which reduced to 115 mPa s when 40% of the HEMA diluent was added. Furthermore, thermal, mechanical, coating, and swelling properties of the resulting UV-cured C-PUA/HEMA materials were investigated. The ultimate biomaterials showed excellent performance, including a glass transition temperature (T(g)) of 74–123 °C, maximum thermal degradation temperature of 437–441 °C, tensile strength of 12.4–32.0 MPa, tensile modulus of 107.2–782.7 MPa, and coating adhesion of 1–2. In conclusion, the developed C-PUA resins show great potential to be applied in UV-curable materials like coatings.